2015
DOI: 10.1007/s10570-015-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and catalytic performance of Fe(III)-citric acid-modified cotton fiber complex as a novel cellulose fiber-supported heterogeneous photo-Fenton catalyst

Abstract: Woven cotton fabric was first modified with citric acid by a conventional pad-dry-cure process and then coordinated with Fe(III) ions to prepare a Fe(III)-modified cotton fiber complex. After the characterization by SEM, FTIR, XPS, XRD and DRS, this complex was used as a heterogeneous Fenton catalyst for the degradation of a typical textile dye, Acid Red 88, under visible irradiation. Some factors affecting the modification process, such as the citric acid and NaH 2 PO 4 concentrations as well as the curing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The organic polymeric ligands and center metal ions are the key for the fabrication of these PMCs. Fiber metal complexes as the attractive PMCs have been used as the catalysts in some chemical reactions, especially in Fenton system for the degradation of organic pollutants due to their easy separation, recycling, and controllable tailoring . Another advantage is that the use of textile technology allowing the manufacture of inexpensive fibrous materials from synthetic fiber complex in the form of woven cloth and bulky knit fabrics .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic polymeric ligands and center metal ions are the key for the fabrication of these PMCs. Fiber metal complexes as the attractive PMCs have been used as the catalysts in some chemical reactions, especially in Fenton system for the degradation of organic pollutants due to their easy separation, recycling, and controllable tailoring . Another advantage is that the use of textile technology allowing the manufacture of inexpensive fibrous materials from synthetic fiber complex in the form of woven cloth and bulky knit fabrics .…”
Section: Introductionmentioning
confidence: 99%
“…The optimized design and synthesis of novel polymer metal complexes (PMCs) have attracted great attention in the past two decades due to their intriguing variety of topologies and potential applications as functional materials for molecular adsorption, luminescence, heterogeneous catalysis, and so on. [1][2][3][4][5][6][7][8][9][10][11] The organic polymeric ligands and center metal ions are the key for the fabrication of these PMCs. Fiber metal complexes as the attractive PMCs have been used as the catalysts in some chemical reactions, especially in Fenton system for the degradation of organic pollutants due to their easy separation, recycling, and controllable tailoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among AOPs, the Fenton process offers an effective source of hydroxyl radicals to decompose organic pollutants and is easily operated. However, the homogeneous Fenton process is restricted by the strict control of the pH around 2-3 and the disposal of large amount of iron sludge (Elshafei et al, 2010;Bai et al, 2013).To overcome these problems, the heterogeneous Fenton process with Fe(II)/Fe(III) complexes has been used to remove organic pollutants (Lin and Wu, 2005;Elshafei et al, 2010;Bai et al, 2013;Li et al, 2015a;Manenti et al, 2015). It can be observed that the removal rate of organics is higher for the homogeneous Fenton process than heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the reaction time of the homogeneous Fenton process is faster than heterogeneous. It was found that the degradation efficiency of the heterogeneous Fenton process was accelerated under the acidic condition, UV and visible light irradiation (Li et al, 2015a;Manenti et al, 2015). Therefore, the development of novel heterogeneous Fenton catalysts, used in the alkalic and neutral conditions with high catalytic activity and stability and low cost, has become the most important issue.…”
Section: Introductionmentioning
confidence: 99%